Study on Mechanical Behaviors of Variable-Stiffness Composite Laminates. Issue 3 (March 2014) - Zhonghai, Xu; Zhe, Liu; Xiaojing, Lv; Hongtao, Ma; Lifeng, Hao; Weicheng, Jiao; Fan, Yang; Rongguo, Wang
In this paper, we study the mechanical behaviors of variable-stiffness composite laminates by setting curvilinear fiber paths. We assume that the fiber orientation angles vary linearly with the reference axis. Based on the different fiber paths, we vary the fiber placement formats and the curvilinear fiber orientation angles of the composite laminates, and then make the simulation for the buckling loads of the three kinds of laminates: the straight fiber placement, the curvilinear fiber placement and the mixed fiber placement. By comparing and analyzing, we give the best fiber placement format and the curvilinear fiber orientation angle. The study provides references to the design of variable-stiffness composite laminates.